2021
DOI: 10.1155/2021/9962429
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Missed Canals and Their Association with Apical Periodontitis in Posterior Endodontically Treated Teeth: A CBCT Study

Abstract: Background. This study aimed to assess the prevalence of missed canals in endodontically treated teeth and their association with apical periodontitis in a Saudi Arabian population using CBCT. Materials and Methods. A total of 208 CBCT radiographs were investigated. For each tooth, radiographs of axial, coronal, and sagittal segments were acquired to appraise the external as well as the internal structure of the root canal system and apical area. In root canal-treated teeth, unfilled canals appearing from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
3
14
1
5
Order By: Relevance
“…Hoen and Pink [ 8 ] detected untreated canals in 42% of all non-surgically retreated teeth. Moreover, Karabucak et al [ 7 ] reported a 23% overall frequency, while Mashyakhy et al [ 19 ] found an 18% overall prevalence of untreated canals. Costa et al [ 6 ] and Baruwa et al [ 5 ] found a lower prevalence of 12%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hoen and Pink [ 8 ] detected untreated canals in 42% of all non-surgically retreated teeth. Moreover, Karabucak et al [ 7 ] reported a 23% overall frequency, while Mashyakhy et al [ 19 ] found an 18% overall prevalence of untreated canals. Costa et al [ 6 ] and Baruwa et al [ 5 ] found a lower prevalence of 12%.…”
Section: Discussionmentioning
confidence: 99%
“…Baruwa et al [ 5 ] and Karabucak et al [ 7 ] reported 82.6% and 82.8% of untreated canals associated with AP, respectively. Furthermore, Mashyakhy et al [ 19 ] and Costa et al [ 6 ] found a very high incidence of AP (90% and 98%, respectively) among teeth with untreated canals. All previous investigations [ 5 - 7 , 19 ] have illustrated a strong association between untreated canals and AP compared to the current findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations